FAKTOR PENENTU KEPUTUSAN USAHATANI TEMBAKAU: PENDEKATAN “BEHAVIORAL REASONING THEORY” - Dwi Lilik Kholifatun; Badi atud Durroh; Fina Sulistiya Ningsih (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Market uncertainty and fluctuating tobacco prices influence farmers’ decisions in managing their farming businesses. This study was conducted because, despite facing high economic risks, farmers continue to choose tobacco cultivation, making it important to understand the factors that influence such decisions. The research was carried out in Sukosewu District, Bojonegoro Regency. The aim of this study is to identify the factors affecting tobacco farmers’ decision-making using the Behavioral Reasoning Theory (BRT) approach, which includes the variables of values, reasons for, reasons against, and farming decisions. The analysis method used in this study is SEM (Structural Equation Modeling) with Partial Least Squares (PLS) as the analytical tool. The results indicate that all three variables significantly influence farming decisions, with values having the greatest impact due to the strong social, cultural, and economic values inherent in the lives of tobacco farmers in Sukosewu.